A study of the association between alcohol consumption, road accidents, learning behavior and academic achievement in university students: การดื่มแอลกอฮอล์และผลลัพธ์ทางสุขภาพและการเรียนในนักศึกษา - A, Rojanasumapong; K, Suparan; J, Wongsuthipol; T, Hiranwong; K, Pinyopornpanish; C, Angkurawaranon; W, Jiraporncharoen (Biomedical Sciences and Clinical Medicine, 2019)
Objective The purpose of this study was to explore if there was an association between alcohol consumption, health outcomes (risky behavior and experience of alcohol-related accidents), learning behavior and academic achievement among university students. Methods This cross-sectional study was performed on random samples of Chiang Mai University students who were willing to participate. A convenience sampling technique was used. The study was conducted from 14 September 2017 to 17 October 2017. The data collected from the participants was analysed using a descriptive statistic. The association between the variables was assessed using the One-Way ANOVA test and the Chi-Square test. Results The average age of participants was 20 years old (Mean 20.28 SD 0.06). There were 221 females (51.4%) in this group. The prevalence of drinking was 81.86%. The prevalence of males who drink at least once a month was higher than in females (40.78% in males and 21.72% in females). An increase in alcohol consumption was related to drinking and driving (p<0.001) and alcohol-related accidents (p=0.036). An increase in alcohol consumption was also related to lower GPA (p<0.001), classes skipping (p<0.001), being late for classes (p<0.001) and withdrawing from courses (p<0.001). No association was found between alcohol consumption and attitudes toward academic study. Conclusion The prevalence and frequency of alcohol consumption was higher in the male group.Alcohol consumption was associated with poorer health outcomes and lower academic achievement.